Interpersonal comparisons of utility: an algebraic characterization of projective preorders and some welfare consequences - Juan Carlos Candeal; Esteban Induráin; José Alberto Molina (Institute for the Study of Labor (IZA), 2007)
It is shown that any completely preordered topological real algebra admits a continuous utility representation which is an algebra-homomorphism (i.e., it is linear and multiplicative). As an application of this result, we provide an algebraic characterization of the projective (dictatorial) preorders defined on Rn. We then establish some welfare implications derived from our main result. In particular, the connection with the normative property called independence of the relative utility pace is discussed.
urn:nbn:de:101:1-20080422267
Keywords: 330; Interpersoneller Nutzenvergleich; Nutzenfunktion; Theorie